RE: Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - Rasim Eren Cankurtaran; Yasin Celal Güneş; Emre Dirican; Oktay Algın; Damla Cankurtaran; Öykü Tayfur Yürekli (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Cankurtaran RE, Güneş YC, Dirican E, Algın O, Cankurtaran D, Tayfur Yürekli Ö. RE: Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):75.